2012
DOI: 10.1128/iai.06295-11
|View full text |Cite|
|
Sign up to set email alerts
|

Reactive Oxygen Species-Triggered Trophoblast Apoptosis Is Initiated by Endoplasmic Reticulum Stress via Activation of Caspase-12, CHOP, and the JNK Pathway in Toxoplasma gondii Infection in Mice

Abstract: dToxoplasma gondii infection in pregnant women may result in abortion or in fetal teratogenesis; however, the underlying mechanisms are still unclear. In this paper, based on a murine model, we showed that maternal infection with RH strain T. gondii tachyzoites induced elevated production of reactive oxygen species (ROS), local oxidative stress, and subsequent apoptosis of placental trophoblasts. PCR array analysis of 84 oxidative stress-related genes demonstrated that 27 genes were upregulated at least 2-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…This is in agreement with previous reports that in Toxoplasma gondii infection, ROS-triggered trophoblast apoptosis is initiated by ER stress via activation of the JNK pathway along with caspase-12 and CHOP (52). A study demonstrated that fenretinide, a synthetic retinoid with antitumor activity, induced PLAB protein upregulation involving ROS generation, ER stress induction, and JNK activation (53).…”
Section: Discussionsupporting
confidence: 80%
“…This is in agreement with previous reports that in Toxoplasma gondii infection, ROS-triggered trophoblast apoptosis is initiated by ER stress via activation of the JNK pathway along with caspase-12 and CHOP (52). A study demonstrated that fenretinide, a synthetic retinoid with antitumor activity, induced PLAB protein upregulation involving ROS generation, ER stress induction, and JNK activation (53).…”
Section: Discussionsupporting
confidence: 80%
“…It was demonstrated that NADPH oxidase (NOX)-derived ROS plays an essential role in inflammatory responses and has antiparasite activity against T. gondii (19,20). Additionally, ROS generation with T. gondii is essential for mammalian innate immunity and acts through the phosphatidylinositol 3-kinase (PI3K)/AKT (19), endoplasmic reticulum (ER) stress, apoptosis, or JNK pathway (21). However, the roles of TRAF6 and ROS in the regulation of GRA7-induced intracellular signaling and innate immune responses are largely uncharacterized.…”
mentioning
confidence: 99%
“…[23] Glutathione is the most abundant non-protein thiol source in the cell, which acts as a substrate for several enzymes, including glutathione peroxidase and GST and serves multiple functions in protecting tissues from oxidative damage and keeping the intracellular environment in the reduced state. [17,23] A significant depletion of glutathione and glutathione peroxidase activity were noted in the present study in serum of women infected with T. gondii which was the result of high oxidative stress and both antioxidants over-use by the cells .Moreover, the low glutathione levels, especially in the infected pregnant women with acute phase of toxoplasmosis, represent a decreased detoxicating capacity of pregnant [25] The decreased in level in serum of toxoplasmosis patients has been demonstrated [20,21,26] The present study showed no significant differences in albumin ratio in seropositive Toxoplasmosis woman and this result is consistent with the of previous study. [23] But Boothroyd et al [27] observed that toxoplasmosis led to an increase in serum protein and globulin concentrations and a decrease in serum albumin concentrations during the acute stage and decrease of albumin in the acute stage which indicates decrease in protein metabolism or increase catabolism.…”
Section: Discussionmentioning
confidence: 80%
“…Seventy six blood samples were collected from seropositive-Toxoplasmosis women and from (25) seronegative Toxoplasmosis women (Control group). Age range: 16-46 years old and who had been referred to Tikrit hospital in Salaheldin from September 2013 until March 2014.…”
Section: Methodsmentioning
confidence: 99%